Change of proteolysis and sensory profile during ripening of Cheddar‐style cheese as influenced by a microbial rennet from rice wine. Issue 4 (25th March 2019) - Zhao, Xiao; Zheng, Zhe; Zhang, Jian; Sarwar, Abid; Aziz, Tariq; Yang, Zhennai
Abstract: To test the potential of a novel microbial rennet isolated from traditional fermented rice wine for cheese making, Cheddar‐style cheese made with this enzyme was studied for changes in composition, proteolysis, and sensory profile during 90 days of ripening in comparison with a control cheese made with a commercial rennet. The initial proteolysis assay of the microbial rennet on milk proteins indicated a notable increase in the hydrolysis of casein components (α‐, β‐, and κ‐caseins) but no effect on whey proteins upon increasing the concentration of the enzyme. Correspondingly, compared to cheese made with commercial rennet, the use of the microbial rennet in Cheddar‐style cheese resulted in significantly higher primary and secondary proteolysis in the later stages of ripening (60–90 days ripening) and thus a softer texture and the formation of more volatile compounds and free amino acids (FAAs) despite its lower moisture content (41.7%, w/w). Though the cheese made with the microbial rennet was found to contain bitter‐taste FAAs (1, 000 mg/100 g), the combined effect of other‐taste FAAs, including sweet (231 mg/100 g), umami (225 mg/100 g), and tasteless (361 mg/100 g) FAAs, in the cheese attenuated the bitter taste of the cheese. This analysis was in accordance with the sensory evaluation, which showed no significantly different sensory scoring between the cheeses made with the microbial and commercial rennets. The present study demonstrated a novel approach to evaluate the bitter taste of ripened cheese. The results of this study suggest the potential of the microbial rennet from rice wine to serve as a new source of milk‐clotting agents in cheese making. Abstract : The microbial rennet isolated from glutinous rice wine was evaluated in making Cheddar‐style Cheese MR. The use of microbial rennet caused more proteolysis and accelerated ripening of cheese with more volatile formation. Cheese MR showed good sensory acceptability without obvious bitter taste.